Upaya Meningkatkan Hasil Penyusunan Rencana Pelaksanaan Pembelajaran Melalui Bimbingan Kepala Sekolah Di SMAN 70 - Budiarti, Ratna (Universitas Cokroaminoto Yogyakarta, 2023)
This research examines the importance of coaching to make a breakthrough by providing guidance on an ongoing basis to teachers at SMA Negeri 70 Kebayoran Baru, South Jakarta, with the hope that later it will produce (output) teachers who are able to master how to prepare lesson plans properly and correctly. The results of the study show that continuous guidance can increase teacher motivation in compiling a complete lesson plan. The teacher shows seriousness in understanding and compiling lesson plans, especially after receiving guidance on the development/composition of lesson plans from researchers. This information the researchers obtained from the results of observations when conducting interviews and guidance on the development / preparation of lesson plans for teachers. Next is to show that continuous guidance can improve teacher competence in preparing lesson plans. This can be proven from the results of observations which show that there is an increase in teacher competence in preparing lesson plans from cycle to cycle. In the first cycle, the average value of lesson plan components was 69% and in the second cycle, 83%. So, there was an increase of 14% from cycle I.